Clinical and Histopathological Correlation of Quantitative HBsAg Levels in Chronic Hepatitis B - Yilmaz, Turgay; Ozdemir, Erdogan; Duzenci, Deccane; Bahcecioglu, Ibrahim Halil (Wiley, 2025)
Objective: This study is aimed at comparing different clinical forms of chronic hepatitis B (CHB) infection (HBeAg-negative chronic HBV infection and HBeAg-positive and HBeAg-negative CHB patients) and evaluate their demographic, laboratory, virological, and histopathological characteristics, as well as investigate the relationship between quantitative HBsAg (qHBsAg) levels and these parameters. Materials and Methods: This prospective study included a total of 307 patients, comprising 142 HBeAg-negative chronic HBV infection and 165 CHB patients (39 HBeAg-positive and 126 HBeAg-negative). Patient data, including age, sex, ALT, AST, GGT, ALP, total bilirubin, HBV DNA, and qHBsAg levels, were recorded. Additionally, liver biopsy was performed in 111 cases (31 HBeAg-positive and 80 HBeAg-negative), and histological activity index (HAI) and fibrosis staging (ISHAK score) were evaluated. Results: No significant differences were observed between HBeAg-negative chronic HBV infection and CHB patients in age and sex distribution. In the CHB group, ALT and HBV DNA levels were significantly higher (p = 0.014 and p = 0.025, respectively). Among CHB patients, HBeAg-positive patients had significantly lower qHBsAg levels than HBeAg-negative patients (1805 vs. 4028 IU/mL, p < 0.001). Histopathological evaluations showed no significant association between qHBsAg levels and fibrosis severity (ISHAK score > 2) or necroinflammatory activity (HAI > 6). ROC analysis confirmed the limited diagnostic value of qHBsAg for advanced fibrosis (AUC 0.511, 95% CI 0.454-0.569). In HBeAg-positive patients, a weak negative correlation was found between qHBsAg and HBV DNA levels (r = -0.388, p = 0.015). Discussion: Our study demonstrated variability in laboratory findings across different forms of CHB. Notably, HBeAg-positive patients exhibited high HBV DNA levels alongside low qHBsAg levels. The limited efficacy of qHBsAg as a fibrosis marker suggests caution in its clinical use. These findings underscore the importance of considering multiple parameters in assessing liver damage.
Keywords: chronic hepatitis B; histopathology; quantitative HBsAg